2021
DOI: 10.1002/adfm.202110432
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Nanozymes: From Matters to Bioapplications

Abstract: The manufacture of bionic materials to simulate the natural counterparts has attracted extensive attention. As one of the subcategories of biomimetic materials, the development of artificial enzyme is intensive pursuing. As a kind of artificial enzyme, nanozymes are dedicated to solve the limitations of natural enzymes. In recent years, attributed to the explosive development of nanotechnology, biotechnology, catalysis science, computational design and theory calculation, research on nanozymes has made great p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
115
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(123 citation statements)
references
References 236 publications
0
115
0
Order By: Relevance
“…In the last two and three years, quite a few studies have demonstrated that well‐defined SACs also show remarkable results in biology and medicine domains via the so‐called “SAzymes” catalysis. [ 242 ] For example, the SAzymes based on single‐atom Fe show dual enzymatic catalytic activity: 1) it can be used as a catalase to achieve ultrasound imaging in tumor site through O 2 generation and 2) it can produce hydroxyl (OH•) radical for chemokinetic therapy with superior peroxidase‐like catalytic activity. [ 243 ] In addition, the ultrasonic radiation or laser excitation can significantly promote the catalytic generation of 1 O 2 by the porphyrin‐based SAzymes (act as acoustic/photosensitized agents), realizing the acoustic and photodynamic therapy.…”
Section: Heterogeneous Catalysis Applications Of Afcsmentioning
confidence: 99%
“…In the last two and three years, quite a few studies have demonstrated that well‐defined SACs also show remarkable results in biology and medicine domains via the so‐called “SAzymes” catalysis. [ 242 ] For example, the SAzymes based on single‐atom Fe show dual enzymatic catalytic activity: 1) it can be used as a catalase to achieve ultrasound imaging in tumor site through O 2 generation and 2) it can produce hydroxyl (OH•) radical for chemokinetic therapy with superior peroxidase‐like catalytic activity. [ 243 ] In addition, the ultrasonic radiation or laser excitation can significantly promote the catalytic generation of 1 O 2 by the porphyrin‐based SAzymes (act as acoustic/photosensitized agents), realizing the acoustic and photodynamic therapy.…”
Section: Heterogeneous Catalysis Applications Of Afcsmentioning
confidence: 99%
“…The description of unexpected enzyme‐like catalytic activities in fullerene derivatives, gold NPs (AuNPs), cerium oxide NPs (nanoceria) and magnetic iron oxide NPs (Fe 3 O 4 NPs) can be found among the earliest report of nanomaterials‐based artificial enzymes, which are commonly referred to as nanozymes today. [ 3,4 ] Recently, Wang's and Yan's groups proposed a new definition of nanozymes: “nanozymes can be defined as nanomaterials that catalyze the conversion of enzyme substrates to products and follow enzymatic kinetics (e.g., Michaelis–Menten) under physiologically relevant conditions, even though the molecular mechanisms of the reactions could be different between nanozymes and the corresponding enzymes.” [ 14 ] Compared to natural enzymes, nanozymes demonstrate many virtues such as robust catalytic efficiency and stability, ease of production and modification, and low manufacturing cost. Moreover, nanozymes can be endowed with additional functionalities that are absent in natural enzymes, including a large surface to volume ratio, responsiveness to external stimuli, and tunable catalytic activities.…”
Section: Nps As Mimics Of Enzymesmentioning
confidence: 99%
“…Nanozymes, new emerging inorganic nanocatalysts as the alternatives of natural enzymes, mimick the catalytic behavior of natural enzymes and exhibit diverse applications in the field of food science, environmental remediation, clinical diagnosis, and disease therapy [1][2][3][4][5][6]. This concept is originated from a pioneer investigation of magnetic Fe 3 O 4 nanoparticles with the peroxidaselike catalytic performance and their potentials for novel immunoassay with three functions of capture, separation, and detection [7]. In comparison with natural counterparts, nanozymes delivered the unique benefits of the high diversity of structures, cost-effective synthesis, high chemical stability, easy storage, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of nanozymes is an interdisciplinary field, which bridges the disciplines of enzymology and heterogeneous catalysis. To date, the catalytic performance of nanozymes is generally analyzed by the Michaelis-Menten equation, in which two parameters of k cat and K m are used to describe the catalytic reaction rate and adsorption affinity of substrates on the surfaces of nanozymes, respectively [7,[26][27][28][29][30]. This method is practically adopted to understand the catalytic kinetics of natural enzymes, which cannot accurately reflect the catalytic mechanism of nanozymes.…”
Section: Introductionmentioning
confidence: 99%